2015
DOI: 10.1074/jbc.m115.646588
|View full text |Cite
|
Sign up to set email alerts
|

CyclinA2-Cyclin-dependent Kinase Regulates SAMHD1 Protein Phosphohydrolase Domain

Abstract: Background: Human sterile ␣ motif and histidine-aspartate domain-containing protein 1 (SAMHD1) is a deoxyribonucleoside triphosphate (dNTP) triphosphohydrolase that is phosphorylated by cyclinA2-dependent kinases. Results: SAMHD1 mutants defective for cyclinA2 binding disrupt S phase progression, and this is alleviated by Thr-592 phosphomimetic mutation. Conclusion: CyclinA2-dependent kinases regulate SAMHD1 activity. Significance: SAMHD1 dNTP phosphohydrolase activity is regulated during the cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(137 citation statements)
references
References 50 publications
10
127
0
Order By: Relevance
“…Previous work by Yan et al showed that pT592 is present in S and G2/M in subpopulations of leukocytes isolated by cell sorting [18]. Here we followed the phosphorylation pattern of T592 during cell cycle progression in synchronized living cells and found that it is intimately linked to kinase and phosphatase activities controlling cell cycle progression.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous work by Yan et al showed that pT592 is present in S and G2/M in subpopulations of leukocytes isolated by cell sorting [18]. Here we followed the phosphorylation pattern of T592 during cell cycle progression in synchronized living cells and found that it is intimately linked to kinase and phosphatase activities controlling cell cycle progression.…”
Section: Discussionmentioning
confidence: 59%
“…In proliferating cells, none of the tested SAMHD1 variants blocked retroviral infection, presumably due to the high expression of RNR that opposed the catabolic activity of SAMHD1[22]. Interestingly, only the non-phosphorylatable SAMHD1 mutants reduced the percentage of cells in S-phase and activated the DNA damage check-point[18]. …”
Section: Introductionmentioning
confidence: 99%
“…The expression of phosphorylation site-mutated SAMHD1 caused cell cycle delay and DNA damage (33). ISF2 is similarly unregulated and thus might be expected to have negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…SAMHD1 phosphorylation by CDK2 is thought to be a means of controlling dNTP levels through the cell cycle (33,34), allowing the dNTP concentration to increase during S and decrease in G 1 /G 0 . The expression of phosphorylation site-mutated SAMHD1 caused cell cycle delay and DNA damage (33).…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots (10 5 cells) of the purified populations were reanalyzed by FACS to assess their purity. The cells were lysed (62,64), and cytoplasmic or chromatin extracts were analyzed by immunoblotting. Detailed experimental procedures are described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%